How women's silence secures the peace: analysing sexual and gender-based violence in a low-intensity conflict. Issue 3 (1st September 2016) - Davies, Sara E.; True, Jacqui; Tanyag, Maria
ABSTRACT: Most studies of the gendered impact of conflict focus on sexual and gender-based violence (SGBV) atrocities committed in high-intensity conflict environments. In contrast, this article focuses on the patterns of SGBV in Mindanao, Philippines – an environment of protracted low-intensity conflict within a fragile state. We examine the current Mindanao peace process to highlight the disempowerment of survivors of SGBV, due in large part to the reporting constraints that affect those most likely to be targeted for sexual violence by rival groups, some of whom are closely associated with the peace process. By making visible the significant social, political-economic, and institutional barriers affecting the recognition and reporting of SGBV, we discuss how and why conflict-related SGBV continues in fragile and low-intensity conflict environments.